The Issue of Computer Art and Technology in the Organization of Independent Gesture in Education - Pahlavonovich , Nabiev Dilshod (International Journal on Human-Computing Studies, 2023)
This article deals with the issue of computer art and technology in the organization of independent work in education scientific-theoretical analysis.